Unlocking Maize (Zea mays) Potential: Exploring Profitability and Marketing Efficiency in Bangladesh’s Char Land Areas. - Begum, S; Acharjee, D C; Gosh, K; Amin, M R; Anik, A R; Alam, G M M (Annals of Bangladesh Agriculture, 2025)
Maize (Zea mays) farming presents a promising opportunity in the char land areas of Bangladesh, characterized by shallow lands that emerge as water levels recede in rivers. However, the geographical remoteness of these regions poses challenges for char farmers in accessing fair prices for their produce. This study endeavors to delve into the determinants of maize profitability and marketing efficiency in the char area. Data were meticulously gathered through a structured survey encompassing 200 maize farmers and 40 market actors across four villages in Gangachara upazila, Rangpur district, in 2022. Employing descriptive statistics and multiple regression methods, we aim to analyze the factors affecting maize profitability, assess existing maize marketing chains and costs, and examine maize marketing efficiency in the char area. Our findings underscore the profitability of maize cultivation, with a Benefit-Cost Ratio (BCR) of 1.57. Small farms maximize returns, while medium-sized farms benefit from cost advantages despite lower yields, showing a discernible correlation between farm size, higher yields, and profits. Moreover, our investigation reveals that maize profitability is significantly influenced by farm size, seed and fertilizer costs, land preparation, and irrigation expenses. Furthermore, we shed light on the intricate maize supply chain, identifying Chain II (includes Farmers to aratdar to feed mills to Processor) as the most efficient, boasting the highest producer share and the lowest marketing cost. Notably, wholesalers faced the highest marketing costs, amounting to BDT 146 per quintal, while faria (local traders) experienced the lowest costs at BDT 81 per quintal. To enhance maize production, profitability, and livelihoods of char farmers, we urge for government intervention in the form of providing subsidized hybrid seeds and fertilizers to bridge yield gaps across farm sizes, reducing irrigation costs through subsidized infrastructure or collective irrigation systems, alongside easy access to low-interest credit to manage input costs. Promoting direct farmer-to-aratdar sales (Chain II) by establishing cooperative marketing facilities could reduce costs and enhance producer shares. Additionally, improving rural road networks would minimize transportation expenses for farmers, particularly those selling through less efficient marketing chains. These targeted interventions aim to address identified inefficiencies and promote sustainable maize farming practices while enhancing the livelihoods of char communities. Ann. Bangladesh Agric. 28(1): 61-77